2021
DOI: 10.3389/fpsyt.2021.707916
|View full text |Cite
|
Sign up to set email alerts
|

Applying Machine Learning Approaches to Suicide Prediction Using Healthcare Data: Overview and Future Directions

Abstract: Objective: Early identification of individuals who are at risk for suicide is crucial in supporting suicide prevention. Machine learning is emerging as a promising approach to support this objective. Machine learning is broadly defined as a set of mathematical models and computational algorithms designed to automatically learn complex patterns between predictors and outcomes from example data, without being explicitly programmed to do so. The model's performance continuously improves over time by learning from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 27 publications
0
12
0
3
Order By: Relevance
“…Participants underwent deep phenotyping that included an in-person clinical interview (for participants older than 10), and interview with the primary caregiver (for participants aged [8][9][10][11][12][13][14][15][16][17]. Thus, ages 8-10 received only caregiver interviews and ages 11-17 received both caregiver and self-report.…”
Section: Baseline Pnc Assessment (T1 Mean Age 111 Years Conducted 200...mentioning
confidence: 99%
See 1 more Smart Citation
“…Participants underwent deep phenotyping that included an in-person clinical interview (for participants older than 10), and interview with the primary caregiver (for participants aged [8][9][10][11][12][13][14][15][16][17]. Thus, ages 8-10 received only caregiver interviews and ages 11-17 received both caregiver and self-report.…”
Section: Baseline Pnc Assessment (T1 Mean Age 111 Years Conducted 200...mentioning
confidence: 99%
“…Research is now in the phase of determining the optimal way of leveraging such prediction algorithms into translational tools (14). A few promising studies suggest that ML predictive modeling can yield predictions of clinical relevance (15), mostly relying on the electronic health record [EHR] (16). Predicting SA in youth based on EHR data may be challenging, because the information contained in the average youth’s EHR is substantially less extensive than that contained in the typical adult’s EHR.…”
Section: Introductionmentioning
confidence: 99%
“…They have been widely used in engineering and scientific research fields. With the development of AI and computer technology, there is a few of research have tried to apply the machine learning method to suicide and suicide attempt ( Mezuk et al, 2018 ; Ryu et al, 2019 ; Chen et al, 2020 ; Gradus et al, 2020 ; Boudreaux et al, 2021 ). But there are few studies establishing the prediction model for suicide using the ANN.…”
Section: Introductionmentioning
confidence: 99%
“…For the past 50 years, extensive work has been conducted to improve the prediction of suicide, yet a recent published meta-analysis demonstrated that using known suicide risk factors leads to modest results (weighted area under the receiver operating characteristic curve [AUC], 0.58) ( 2 ). Several factors may have led to this prediction failure ( 3 ). Firstly, suicidal rate in the population is relatively low, making prospective studies not practical ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, prior studies were often limited to small samples, measured at a single time point, and examined few number of factors. Finally, the traditional method for statistical analysis of the suicide data mainly focus on inference, which resulted in simple prediction models; lastly, they are not designed to incorporate new clinical data to continuously update the existing models ( 3 ).…”
Section: Introductionmentioning
confidence: 99%